Exploration and exploitation in mergers and acquisitions: An empirical study of the electronics industry in Taiwan. Issue 1 (4th March 2014) - Lin, Liang-Hung
Abstract : Purpose: – The central concern of organizational learning and corporate strategy has, in recent decades, focused on the rational choice and appropriate balance between exploration and exploitation. Dividing mergers and acquisitions (M&As) into related and unrelated M&As, this study applies the exploration vs exploitation construct to examine how different M&A strategies affect exploration and exploitation of the combined firm, how post-acquisition integration affects exploration and exploitation of the combined firm, and how organizational ambidexterity affects post-acquisition performance. The paper aims to discuss these issues. Design/methodology/approach: – Organizational and industry level data were drawn from the top 1, 000 Taiwanese electronic and computer firms reported by 2009 China Credit Information Service, an authorized credit-rating company in Taiwan. The companies are classified into four industries: computer and associated equipments manufacturing (SICs 271x, 274x, 276x); integrated circuits (SIC 261x), opto-electronics and telecommunication (SICs 264x, 272x, 277x) and electronic components (SICs 262x, 263x, 264x, 269x, 275x). Questionnaires were distributed to general managers of the top 1, 000 electronics companies. Findings: – This investigation of Taiwanese electronic and computer firms revealed that related acquisitions with high degrees of acquisition integration positively affect the combined firm's exploitation; unrelated acquisitions with high degrees of R&D expenditure and acquisition experience positively affect the combined firm's exploration. The firm's ability of simultaneously pursuing exploitation and exploration positively affects its post-acquisition performance. Originality/value: – The contribution of this study is to understand how acquisitions influence exploitation and exploration. With regard to the relationship between acquisition and exploitation/exploration, this study finds that unrelated acquisitions enhance exploration, whereas related acquisitions enhance exploitation.